Plasma Membrane Ca2+–ATPase in Rat and Human Odontoblasts Mediates Dentin Mineralization - Maki Kimura; Hiroyuki Mochizuki; Ryouichi Satou; Miyu Iwasaki; Eitoyo Kokubu; Kyosuke Kono; Sachie Nomura; Takeshi Sakurai; Hidetaka Kuroda; Yoshiyuki Shibukawa (Biomolecules, 2021)
Intracellular Ca2+ signaling engendered by Ca2+ influx and mobilization in odontoblasts is critical for dentinogenesis induced by multiple stimuli at the dentin surface. Increased Ca2+ is exported by the Na+–Ca2+ exchanger (NCX) and plasma membrane Ca2+–ATPase (PMCA) to maintain Ca2+ homeostasis. We previously demonstrated a functional coupling between Ca2+ extrusion by NCX and its influx through transient receptor potential channels in odontoblasts. Although the presence of PMCA in odontoblasts has been previously described, steady-state levels of mRNA-encoding PMCA subtypes, pharmacological properties, and other cellular functions remain unclear. Thus, we investigated PMCA mRNA levels and their contribution to mineralization under physiological conditions. We also examined the role of PMCA in the Ca2+ extrusion pathway during hypotonic and alkaline stimulation-induced increases in intracellular free Ca2+ concentration ([Ca2+]i). We performed RT-PCR and mineralization assays in human odontoblasts. [Ca2+]i was measured using fura-2 fluorescence measurements in odontoblasts isolated from newborn Wistar rat incisor teeth and human odontoblasts. We detected mRNA encoding PMCA1–4 in human odontoblasts. The application of hypotonic or alkaline solutions transiently increased [Ca2+]i in odontoblasts in both rat and human odontoblasts. The Ca2+ extrusion efficiency during the hypotonic or alkaline solution-induced [Ca2+]i increase was decreased by PMCA inhibitors in both cell types. Alizarin red and von Kossa staining showed that PMCA inhibition suppressed mineralization. In addition, alkaline stimulation (not hypotonic stimulation) to human odontoblasts upregulated the mRNA levels of dentin matrix protein-1 (DMP-1) and dentin sialophosphoprotein (DSPP). The PMCA inhibitor did not affect DMP-1 or DSPP mRNA levels at pH 7.4–8.8 and under isotonic and hypotonic conditions, respectively. We also observed PMCA1 immunoreactivity using immunofluorescence analysis. These findings indicate that PMCA participates in maintaining [Ca2+]i homeostasis in odontoblasts by Ca2+ extrusion following [Ca2+]i elevation. In addition, PMCA participates in dentinogenesis by transporting Ca2+ to the mineralizing front (which is independent of non-collagenous dentin matrix protein secretion) under physiological and pathological conditions following mechanical stimulation by hydrodynamic force inside dentinal tubules, or direct alkaline stimulation by the application of high-pH dental materials.